Burden of hospitalizations due to Rotavirus infection in Emilia Romagna, Italy - Gabutti, G.; Lazzara, C.; Marsella, et al., M. (Acta Biomedica Atenei Parmensis, 2007)
The aim of this study was to collect data on hospitalizations due to gastrointestinal diseases, in particular Rotavirus gastroenteritis (RVGE), in the Region of Emilia Romagna, Italy. The national hospital discharge database was used to evaluate the epidemiology of RV infections in the 2000-2003 period, analyzing only the principal diagnosis. The available age groups were 0-14 years, 15-64 years and, >64 years. Hospitalization related costs were estimated through Diagnosis Related Group (DRG) rates even though a specific DRG for RVGE does not exist. In the 0-14yr. old subjects, RV were responsible for an average of 310 GE-related hospitalizations per year and globally represented 17% of admissions for enteritis and 84% of hospitalized viral GE. Fifty-six percent of the enteritis was of undefined origin. Considering the three possible DRG codes to which the disease can be referred (184, 298, 422) and the classification of hospitals in two categories, the cost of each admission for RVGE ranged between 1,293.83 ¶ and 2,263.79 ¶. RV seems to play an important role as a cause of severe viral gastroenteritis, although RV infections are certainly underestimated for several reasons, one of them being the low sensitivity of hospital discharge forms.Today we have safe and effective vaccines that can be used in order to protect from moderate/severe forms of RV-related diarrhea. The extensive use of these vaccines could reduce hospitalizations and related costs in industrialized countries.